Analisis Sosio-Legal terhadap Praktik Perkawinan Usia Dini: Studi pada Masyarakat Pedesaan - Muh. Sudirman; Irsyad Dahri; Nurwana Nurwana (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
This study aims to analyze the legal provisions of marriage in relation to early marriage practices, identify their causal factors, and examine community responses to such practices in Pallawa Village, Tellu Limpoe District, Bone Regency. The research employs a qualitative approach using a case study design. Data were collected through interviews and documentation involving village officials, community members, and individuals engaged in early marriage. The findings indicate that Article 7 paragraph (1) of Law Number 1 of 1974, as amended, stipulates that the minimum legal age for marriage for both males and females is 19 years. Nevertheless, early marriages continue to occur through marriage dispensation granted by the Religious Court. The primary contributing factors include promiscuity, economic pressure, premarital pregnancy, and personal desire. In general, community members express disapproval of early marriage because it contradicts legal regulations and is considered to have potential negative social, psychological, and educational impacts on couples. These findings highlight a gap between legal norms and social realities, suggesting the need for strengthened legal awareness, family guidance, and institutional intervention to reduce early marriage rates and promote compliance with marriage law provisions.